Lazer-solimini equation with state-dependent delay: an alternative demonstration (2013)
In this paper, an alternative proof of results in [6] is given; there, the existence of T-periodic solutions of a family of Lazer-Solimini equations with state-dependent delay is studied. The tools used in the proof are a combination of a priori bounds and coincidence degree.